Cardiovascular Outcomes and Proprotein Convertase Subtilisin/Kexin Type 9 Inhibitors: Current Data and Future Prospects - Duprez, Daniel A (Vasc Health Risk Manag, 2020)
Cardiovascular (CV) disease remains the leading cause of morbidity and mortality worldwide and poses an ongoing challenge with the aging population. Elevated low-density lipoprotein cholesterol (LDL-C) is an established risk factor for atherosclerotic cardiovascular disease (ASCVD), and the expert consensus is the use of statin therapy (if tolerated) as first line for LDL-C reduction. However, patients with ASCVD may experience recurrent ischemic events despite receiving maximally tolerated statin therapy, including those whose on-treatment LDL-C remains ≥70 mg/dL, patients with familial hypercholesterolemia, high-risk subgroups with comorbidities such as diabetes mellitus, and those who have an intolerance to statin therapy. Optimal therapeutic strategies for this unmet need should deploy aggressive lipid lowering to minimize the contribution of dyslipidemia to their CV risk, particularly for very high-risk populations with additional risk factors beyond hypercholesterolemia and established ASCVD. To understand the current clinical climate and guidelines regarding ASCVD, we primarily searched PubMed for articles published in English regarding lipid-lowering therapies and CV risk reduction, including emerging therapies, and CV outcomes trials with proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors. This review discusses the findings of recent clinical trial evidence for CV risk reduction with cholesterol-lowering therapies, with a focus on CV outcomes trials with PCSK9 inhibitors, and considers the impact of the study results for secondary prevention and future strategies in patients with hypercholesterolemia and CV risk despite maximally tolerated statin therapy.